Microsoft Exchange Server 2003 delta guide - McAmis, David (Delta Guide Ser., 2003)
The Delta Guide to Exchange 2003 has been designed to become an invaluable resource to existing Exchange administrators, allowing you to quickly come up to speed on new features and functionality in Exchange, building on the knowledge and experience you already possess. The "Delta" series is designed to allow IT professionals to quickly update your skills based on what has changed between the previous and current software release. This book is for you if you are a system administrator who is responsible for administering a previous Exchange installation (v5.5 or 2000) or if you are an IT professional who has some experience with a previous version of Exchange and wish to update your skills. This book covers changes in installation, configuration, administration, clustering, security and many other important topics.